Determinan yang Mempengaruhi Tax Saving pada Klasifikasi Industri Consumer Goods di Indonesia - Meylinda Marditasari; Shinta Permata Sari (Perspektif Akuntansi, 2021)
Taxes are the largest source of national income, but tax payable could burden and reduce corporare profit. Tax saving is company’s ability to save tax payable in line with giving attention to the stakeholder point of view about manager’s performance in managing the company. This study aims to examine the determinant factors: capital structurw, sales growth, depreciation, and the audit committee’s financial expertice that affect tax saving. The population of tis study is companies in te consumer goods industry classification that are listed on the Indonesia Stock Exchange in 2017-2019. The sample dertermines using purposive sampling and there are 69 company’s data that met the criteria. This study uses secondary data and the hypothesis is tested using multiple linier regression analysis. The results of hypothesis testing show that sales growth and depreciation affect tax saving. Meanwhile, capital structure and audit committee’s financial expertise do not affect tax saving